2022
DOI: 10.3389/fmars.2022.1035140
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific differences and ecological correlations of ultraviolet radiation tolerance in low- and high-altitude fishes

Abstract: Ultraviolet radiation (UVR) is a ubiquitous environmental factor and with complex and diverse effects on organisms, and the UVR tolerance of species varies due to selection, adaptation and evolution. This study aimed to improve our understanding of the interspecific differences in UVR tolerance of fishes. First, we compared skin histology between high-altitude fishes and their low-altitude relatives. Second, we assessed the skin histological changes of 22 fish species after UVR exposure and quantified their da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…The tolerance of Schizothorax davidi to low temperature and UVR was slightly stronger than that of Spinibarbus sinensis, but its salinity tolerance was the weakest among the six species. As a carnivorous fish, Percocypris pingi has a higher oxygen consumption rate under emergency conditions (Bau and Parent, 2001), and histological sections showed that the density of mucous cells and club cells in its epidermis was higher, while the epithelial cells that play a major role in resisting UVR were thinner (Gu et al, 2022a;Gu et al, 2022b). Therefore, its tolerance to low oxygen and UVR was slightly lower than that of Schizothorax davidi with similar altitude distribution.…”
Section: Factors Limiting the Spread Of Lowaltitude Fishes To The Pla...mentioning
confidence: 98%
See 1 more Smart Citation
“…The tolerance of Schizothorax davidi to low temperature and UVR was slightly stronger than that of Spinibarbus sinensis, but its salinity tolerance was the weakest among the six species. As a carnivorous fish, Percocypris pingi has a higher oxygen consumption rate under emergency conditions (Bau and Parent, 2001), and histological sections showed that the density of mucous cells and club cells in its epidermis was higher, while the epithelial cells that play a major role in resisting UVR were thinner (Gu et al, 2022a;Gu et al, 2022b). Therefore, its tolerance to low oxygen and UVR was slightly lower than that of Schizothorax davidi with similar altitude distribution.…”
Section: Factors Limiting the Spread Of Lowaltitude Fishes To The Pla...mentioning
confidence: 98%
“…In our previous studies, we have compared the UVR tolerance of Gymnocypris eckloni, Schizothorax davidi, Spinibarbus sinensis, Luciobarbus capito and Cyprinus carpio (Gu et al, 2022a). In this study, we supplemented the experiment of Percocypris pingi with the same experimental method, and the specific method can refer to our previous research.…”
Section: Uvrmentioning
confidence: 99%